Vendor-Locked DevOps Strategies. - Dunbar, William (Communications of the ACM, 2024)
The article discusses the implications of vendor-locked DevOps solutions, highlighting how specialized solutions tied to one cloud provider can lead to vendor lock-in, hindering the organization's ability to transition effortlessly between providers. It explores the misconception that being cloud-agnostic avoids proprietary constraints, revealing that each cloud has its limitations, necessitating workarounds that may restrict strategic IT goals. Additionally, it compares the advantages and disadvantages of cloud-agnostic and vendor-locked approaches, emphasizing the importance of stakeholders understanding the impact of provider limitations on achieving organizational goals.